2015
DOI: 10.7727/wimj.2013.281
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Deaths in a Nigerian University Hospital: Deaths Too Many

Abstract: Mortalities within 24 hours of presentation at the ED of UCH remain high. This calls for an efficient pre-hospital care, well-organized emergency transport system, new guidelines, establishment of protocols and regular audit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
3
8
0
1
Order By: Relevance
“…In the current study, male deaths constituted 68.0% of all deaths. This is consistent with the findings by Rukewe et al, where 62% of all patient deaths in the ED were male and the findings of Faridaalaee et al, where males constituted 68.0% of patient deaths [11,26].…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, male deaths constituted 68.0% of all deaths. This is consistent with the findings by Rukewe et al, where 62% of all patient deaths in the ED were male and the findings of Faridaalaee et al, where males constituted 68.0% of patient deaths [11,26].…”
supporting
confidence: 93%
“…This rate is relatively low compared to other rates reported in the literature, which ranged from 0.3% to 10.9% in some regions. These data indicate high quality of medical care provided in this department [11,12,21,22].…”
Section: Discussion:-mentioning
confidence: 66%
See 1 more Smart Citation
“…Our study showed 47.3% of death was in between 6-12 hour of arrival followed by 43.6% in 1-6 hours & and 5.5% in less than 1 hour of arrival. Ekere et al found that 70.9 % cases died within 6 hours of arrived in ED and Rukewe et al reported it to be 43.4% within 5 hours of arrival [3,20]. In the limitations of our study, firstly it is a single hospital-based study where patients might be inadequate for critical analysis to meet the objective of the study.…”
Section: Resultsmentioning
confidence: 88%
“…Lekar u primarnoj zdravstvenoj zaštiti mora da bude spreman da upravlja hitnim stanjima kada to zatreba[4], mada je naša ambulanta osobena, jer su u njoj lekari sa iskustvom u radu na terenu i većim iskustvom u zbrinjavanju takvih stanja. Zbog bezbednosti pacijenata i postojanja mogućnosti transporta koja nije svuda dostupna kao na primer u Nigeriji [18] iz naše ambulante većina pacijenata je transportovana uz lekarsku pratnju 88,96%), a samo 11,04% sa vozačem i medicinskim tehničarom, tj transportnom ekipom. U svom radu Martin GD et all, se zalažu za uspostavljanje transportnih protokola između institucija, što bi povećalo kvalitet i dovelo do bolje interhospitalne komunikacije [19].…”
Section: Rezultatiunclassified